2022
DOI: 10.1038/s41598-022-17849-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of facilitatory and inhibitory kinesiotaping of Vastus Medialis on the activation and fatigue of superficial quadriceps muscles

Abstract: This study aimed to investigate how facilitatory and inhibitory KT of the Vastus Medialis affected the activation and the fatigue indices of VM, Vastus Lateralis (VL) and Rectus Femoris (RF) throughout a dynamic fatigue protocol. Seventeen collegiate athletes (Ten males, seven females, age: 24.76 ± 3.99 years, height: 1.73 ± 0.10 m, mass: 68.11 ± 8.54 kg) voluntarily participated in four dynamic fatigue protocol sessions in which no-tape (control condition), inhibitory, facilitatory and sham KTs were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Their findings demonstrated that different types of KT stretches did not modulate the quadriceps isometric strength or single-hop tests in the short or the long term in healthy participants [17,23]. Furthermore, current studies have shown that the direction of KT cannot reduce or enhance muscle activity [24]. A recent study also examined vertical jump performance in healthy young adults failing to find significant differences in jump performance [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings demonstrated that different types of KT stretches did not modulate the quadriceps isometric strength or single-hop tests in the short or the long term in healthy participants [17,23]. Furthermore, current studies have shown that the direction of KT cannot reduce or enhance muscle activity [24]. A recent study also examined vertical jump performance in healthy young adults failing to find significant differences in jump performance [44].…”
Section: Discussionmentioning
confidence: 99%
“…Applying KT at a stretch greater than 50 % can help correct the knee valgus position [19,21] and improve jump performance [18,23]. Other studies have reported limited, inconclusive evidence regarding the effectiveness of KT on muscle strength and functional performance [17,23,24].…”
Section: Introductionmentioning
confidence: 99%